Romania: National Regulations in the Shadow of a Common Past - Dumitru Miheș, Cristian (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
The rule of law is very difficult to enforce during periods of dictatorship or war. We can have a justice system that functions, as we had before 1989, but that system was confined to upholding the regime in power. Romania experienced a dictatorship for a very long period of time. In the first phase, there was a royal dictatorship from 1938, then a military one, followed by the communist regime until the end of 1989. Since 1945, Romania has been a part of the world where the communist system imposed by the Soviet Union left its mark on criminal justice. The authors of the 1968 Penal Code considered that code to have been adopted “with the purpose of solving uniformly the vast problematic of preventing and punishing the crimes.” In a practical regard, the entire legislation was a tool to ensure the success of the regime of communist oppression. In these circumstances, the events that took place in 1989 liberated the spirit of freedom; meanwhile, the consequences of those events took the citizens of the Central and East European countries by surprise, and they were unprepared for the struggle toward democracy and the rule of law. This was the case in Romania when, finally, in 2014, the process of enforcing all fundamental codes was established. In fact, the reform was deeper than the adoption of a new Penal Code, the Code of Criminal Procedure, and the Law on the Execution of Sentences, Educational Measures, and Judicial Measures during Criminal Proceedings. This study presents the main principles, legal institutions, and operational characteristics of the new laws.KEYWORDS: Romania; criminal justice; Penal Code; Code of Criminal Procedure; Law on the Execution of Sentences, Educational Measures, Judicial Measures during Criminal Proceedings